Bioprocessing of biofuels - Sarangi, Prakash Kumar; Nanda, Sonil (Boca Raton : CRC Press, 2021)
"The major issues relating to environmental sustainability such as a heavy dependency on fossil fuels, increased greenhouse gas emissions, pollution, global warming and climate change have drawn much attention around the globe to seek alternative energy sources that have negligible environmental impacts and societal benefits. There is an immense interest in biofuels research around the world due to their massive potentials in addressing the above-mentioned environmental concerns. Biofuels have the potential to supplement the current and future energy demands by being blended with fossil fuels or replacing them completely as drop-in fuels in automobiles as well as heat and power industries. Waste biomass, primarily lignocellulosic biomass (e.g. agricultural crop residues, forestry biomass and energy crops) and microalgae can act as some inexpensive renewable bioresources for the production of biofuels and biochemicals. The prime focus of this book is to shed light on the bioprocessing of biofuels, especially through microbial conversion technologies to recover and transform the inedible polysaccharides into hydrocarbons biofuels and bioenergy. The book offers introductory coverage of the most crucial topics as follows: A systematic overview of the state-of-the-art in the production and utilization of biofuels Categorical bioprospecting of bioresources for biofuel production Biomass pretreatment and enzymatic saccharification Bioconversion of waste biomass and algae to liquid and gaseous biofuels New developments in microbial fuel cell technologies This book is a unification of topics relating to the cutting-edge applications of bioresources and green technologies to reinvigorate the biorefineries in positioning them within a competitive energy market. Persistently fabricated to be instantly applicable, this volume serves as a reference book for undergraduate and graduate students, scientific investigators and research scholars across the globe working in the areas relating to energy and fuels"--
OCLC-licensed vendor bibliographic record.
Keywords: Biomass energy; MEDICAL / Biotechnology; SCIENCE / Biotechnology